Strengthening Early Childhood Development Policies and Programs in Latin America and the Caribbean - Vegas, Emiliana; Silva, Veronica (World Bank, Washington, DC, 2017)
The objective of this Policy Note is to provide a tool for countries in the Latin America and the Caribbean region to take stock of Early Childhood Development (ECD) programs and policies in their territory. By benchmarking against other programs and policies across the region, countries can identify options to strengthen Early Childhood Development. In The Promise of Early Childhood Development for Latin America and the Caribbean, Vegas and Santibanez (2010) put forth key building blocks for countries to achieve comprehensive ECD policies. These building blocks are based on the premise that all countries' share the goal of ensuring that children have adequate experiences during early childhood, which will enable them to reach their full potential during childhood, youth, and into adulthood. Vegas and Santibanez (2010) also document the state of ECD indicators in the region, which show great disparities across countries and within countries.